The Price of Academic Success: Stress and Mental Well-Being of Medical Students - Mroszczyk, Sylwia Maria; Kowalczyk, Zuzanna; Nowicki, Dawid; Muszyńska, Małgorzata; Surowaniec, Julia; Karaś, Katarzyna (Journal of Education, Health and Sport, 2026)
Background. High school graduates are increasingly showing interest in medical studies, particulary in medicine and dentristy. Prospective students most commonly cite a personal interest in medicine as the primary reason for choosing these educational paths. However, studying in medical programs is associated with significant stress, arising mainly from participation in clinical classes and high expectations regarding academic performance. Aim. The aim of this research paper is to present the issue of stress among students of various medical disciplines. Material and methods. This article reviews available literature from 2017 to 2025 concerning stress among students in different medical fields, particularly medical, dental, physiotherapy, and paramedic students. For the purpose of this study, the following databases were used: Elsevier, Google Scholar, and PubMed. Ultimately, 39 articles and 7 online sources were included. Results. Stress is a natural physiological response that arises during change or challenge. It may trigger a wide range of physical, emotional, and behavioral reactions, including the development of depression, anxiety, and impaired cognitive functioning. Identifying sources of stress and factors that exacerbate it enables the development of coping strategies and reduces its negative consequences, which may influence both the quality of future professional decision-making and students’ physical and mental health. Conclusions. Students in medical fields experience high levels of stress, which may lead to mental health problems, burnout, and substance use. They employ adaptive coping strategies, such as active problem-solving and seeking support, while mindfulness-based programs, mentoring, and clinical counseling help reduce stress and improve overall well-being.